Techno-Economic Analysis of Supplier and Shipping Service Selection to Reduce Cost of Goods Sold (Study Case SME XYZ) - Sakti, Arga Seta Asmara (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Indonesia's creative industry, primarily craft, fashion, and culinary, contributes to the country's GDP by 15% annually, with projections estimating it to reach IDR 1,100 trillion by 2020. This growth intensifies industry competition, prompting business owners to compete vigorously to boost sales. SME XYZ wants to implement a cost leadership strategy; businesses must reduce costs, especially in logistics distribution, by reducing operational costs. This study examines the techno-economic analysis of supplier and shipping service selection to reduce the Cost of Goods Sold (COGS) for SME XYZ, a company operating in Indonesia's competitive fashion industry. The research highlights the significant contribution of the creative industry to Indonesia's GDP and the critical role of logistics in maintaining competitive pricing. By employing Total Cost Analysis (TCA), the study evaluates various supplier and transportation combinations, focusing on reducing operational costs while enhancing supply chain efficiency. Field studies and literature reviews provided data on suppliers from Bandung, Jogja, and Malang and logistics services, including JTR, Baraka, and Adex. Results indicate that the optimal combination—Supplier A (Bandung) and Expedition B (Baraka)—reduces COGS from IDR 105.200 to IDR 98.200. The findings offer SME XYZ strategic insights for implementing a cost leadership strategy, ensuring improved operational efficiency and competitive market positioning.